2020
DOI: 10.1111/brv.12675
|View full text |Cite
|
Sign up to set email alerts
|

Motor function recovery: deciphering a regenerative niche at the neuromuscular synapse

Abstract: The coordinated movement of many organisms relies on efficient nerve–muscle communication at the neuromuscular junction (NMJ), a peripheral synapse composed of a presynaptic motor axon terminal, a postsynaptic muscle specialization, and non‐myelinating terminal Schwann cells. NMJ dysfunctions are caused by traumatic spinal cord or peripheral nerve injuries as well as by severe motor pathologies. Compared to the central nervous system, the peripheral nervous system displays remarkable regenerating abilities; ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 173 publications
(234 reference statements)
0
26
0
1
Order By: Relevance
“…Interestingly, studies using different paradigms of peripheral nerve damage have shown that morphological regeneration of the NMJ does not necessarily correlate with motor function recovery [ 22 ]. Likely, the functional rescue of neuromuscular synapses observed in murine species is limited by the denervation time frame and depends on the ability of the cellular components of the neuromuscular synapse to establish a permissive niche for NMJ regeneration [ 2 ]. In this context, our present findings show that NMJ reinnervation of the LAL muscle is accompanied by long-lasting changes in its three cellular components.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, studies using different paradigms of peripheral nerve damage have shown that morphological regeneration of the NMJ does not necessarily correlate with motor function recovery [ 22 ]. Likely, the functional rescue of neuromuscular synapses observed in murine species is limited by the denervation time frame and depends on the ability of the cellular components of the neuromuscular synapse to establish a permissive niche for NMJ regeneration [ 2 ]. In this context, our present findings show that NMJ reinnervation of the LAL muscle is accompanied by long-lasting changes in its three cellular components.…”
Section: Discussionmentioning
confidence: 99%
“…The NMJ is subjected to denervation due to traumatic injuries to peripheral nerves or pathologies. Even though the peripheral nervous system displays a comparatively higher regenerative capacity than the central nervous system, this capability is strongly dependent on the establishment of permissive cellular and molecular niches at the NMJ and the denervation-reinnervation time frame [ 2 ]. Therefore, a deep understanding of the cellular responses that allow proper synaptic function recovery is critical to design strategies to repair and/or to prevent the degeneration of the neuromuscular synapse during the denervation timespan.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of nerve repair is the recovery of target muscle dyskinesia, which depends on the accuracy of motor endplate repair and the plasticity of the neuromuscular junction (NMJ) that is a tripartite, biochemical synapse that can transduce electrical impulses from the brain into voluntary contraction of muscle. [69,70] The plasticity of NMJ is determined by several elements, among which the improvement of repair activity by SCs is the most conducive to axon regeneration. [69] During PNI, SCs release various neurotrophic cytokines to support axon regeneration and nerve function recovery.…”
Section: Mids Upregulate Trkb/bdnf Signaling Contributing To the Prec...mentioning
confidence: 99%
“…One possible mode of action for the loss of AChR clusters could be a direct influence of SC on MN-derived agrin levels. At NMJs, matrix metalloproteinase-3 secreted by terminal SCs was found to cleave agrin and reduce its concentration in the synaptic basal lamina [ 98 , 99 , 100 ]. Conversely, AChR aggregates were increased in matrix metalloproteinase-3 null mice [ 101 , 102 ].…”
Section: Discussionmentioning
confidence: 99%